Mitochondrial dynamics and metabolism across skin cells: implications for skin homeostasis and aging - Martic, Ines; Papaccio, Federica; Bellei, Barbara; Cavinato, Maria (Frontiers in Physiology, 2023)
Aging of human skin is a complex process leading to a decline in homeostasis and regenerative potential of this tissue. Mitochondria are important cell organelles that have a crucial role in several cellular mechanisms such as energy production and free radical maintenance. However, mitochondrial metabolism as well as processes of mitochondrial dynamics, biogenesis, and degradation varies considerably among the different types of cells that populate the skin. Disturbed mitochondrial function is known to promote aging and inflammation of the skin, leading to impairment of physiological skin function and the onset of skin pathologies. In this review, we discuss the essential role of mitochondria in different skin cell types and how impairment of mitochondrial morphology, physiology, and metabolism in each of these cellular compartments of the skin contributes to the process of skin aging.